Liberalism and pluralism : towards a politics of compromise - Bellamy, Richard (Richard Paul) (Routledge, 1999)
In Liberalism and Pluralism the author explores the challenges conflicting values, interests and identities pose to liberal democracy. Richard Bellamy illustrates his criticism and proposals by reference to such topical issues as the citizens charter, constitutional reform, the Rushdie affair and the development of the European Union.